Altis Biologics : from labs to riches? - Gaylard, Alison; Urban, Boris ([London] : SAGE, 2016)
Doctor Nicolaas Duneas was in a quandary: as he sat in his dishevelled office at the Tshwane University of Technology (TUT), he pondered the future of his company Altis Biologics. Founded in 2002, Altis was a small biotechnology company specialising in bone regeneration. Duneas was a trusted expert in his field, and Altis represented his life's work. Now, in July 2009, the company was poised in a kind of no-man's land. Duneas still needed to complete one more set of clinical trials before he could take his product to market, and for that he needed significant capital. Feeling like a very small fish in the big pond of global pharmaceuticals, Duneas wondered just how he was going to find the right funding and strategic partners.
Originally Published in: Gaylard, A. & Urban, B. (2009). Altis Biologics: From Labs to Riches? WBS-2009-15. Johannesburg: The Case Centre, Wits Business School.
Description based on online resource; title from home page (viewed on May 5, 2016).
Keywords: elektronické knihy; electronic books; Fund raising -- Case studies